High Cell Density Cultivation of Paracoccus sp. on Sugarcane Juice for Poly(3-hydroxybutyrate) Production - Moungprayoon, Ayyapruk; Lunprom, Siriporn; Reungsang, Alissara; Salakkam, Apilak (Frontiers in Bioengineering and Biotechnology, 2022)
High cell density cultivation is a promising approach to reduce capital and operating costs of poly(3-hydroxybutyrate) (PHB) production. To achieve high cell concentration, it is necessary that the cultivation conditions are adjusted and controlled to support the best growth of the PHB producer. In the present study, carbon to nitrogen (C/N) ratio of a sugarcane juice (SJ)-based medium, initial sugar concentration, and dissolved oxygen (DO) set point, were optimized for batch cultivation of Paracoccus sp. KKU01. A maximum biomass concentration of 55.5 g/L was attained using the C/N ratio of 10, initial sugar concentration of 100 g/L, and 20% DO set point. Fed-batch cultivation conducted under these optimum conditions, with two feedings of SJ-based medium, gave the final cell concentration of 87.9 g/L, with a PHB content, concentration, and yield of 36.2%, 32.1 g/L, and 0.13 g/g-sugar, respectively. A medium-based economic analysis showed that the economic yield of PHB on nutrients was 0.14. These results reveal the possibility of using SJ for high cell density cultivation of Paracoccus sp. KKU01 for PHB production. However, further optimization of the process is necessary to make it more efficient and cost-effective.